Osvrt na izobrazbu inženjera iz područja motora i vozila na Fakultetu strojarstva i brodogradnje Sveučilišta u Zagrebu - Bjelovučić, Dražen; Jeras, Dušan (Promet - Traffic&Transportation, 2012)
The paper deals with a review of importance of motor cars in the transport and economic system of Croatia with reference to the progressive nations. The review then covers the course of studies fora degree provided by the Department of Engines and Vehicles of the Zagreb University Faculty of Mechanical Engineering and Naval Architecture since the institution of the Engineering School in 1919 to the present. The paper presents the courses of graduate and postgraduate studies. A statistical review is provided of the number of students that have been conferred a Bachelor's, Master's or Doctor's degree in the field of transportation means.